ANTIBAKTERI SENYAWA FENOLIK DARI DAUN SAPUTANGAN (Maniltoa Grandiflora (A. Gray) Scheff) - JHON PATAR SINURAT; SAADAH SIREGAR (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2019)
The Phytochemical screening test to identify secondary metabolites of Saputangan leaves extract (Maniltoa grandiflora (A.Gray) Scheff) showed positive results on phenolic and terpenoid compounds. The reagent used for phenolic screening was 5% FeCl3 and reagent for screening terpenoid was 1% CeSO4 in 10% H2SO4. Antibacterial test was carried out by agar diffusion method on extracts of DMSO Saputangan leaves. Phenolic compound obtained from extract of Saputangan leaves were 36.96 gram where the result was obtained after maceration, partitioning and evaporation processes. Antibacterial of phenolic compound was observed based on inhibitory zone diameters of phenolic compounds formed using paper discs with a diameter of 6 mm. The diameters of the inhibition zone against Escherichia coli bacteria are 8.1; 8.5 and 9.7 mm larger than the diameter of the inhibition zone in Staphylococcus aureus bacteria at 7.3; 7.8 and 8.5 mm. Then it can be stated that DMSO extracts of phenolic compound with concentrations (0.25; 0.50 and 1.00 mg / ml) have antibacterial strength at the medium level where the average inhibition zone of S. aureus bacteria is 7.87 mm and the average inhibition zone in E. coli bacteria is 8.76 mm.